2009
DOI: 10.1016/j.dam.2009.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The Clar formulas of a benzenoid system and the resonance graph

Abstract: a b s t r a c tIt is shown that the number of Clar formulas of a Kekuléan benzenoid system B is equal to the number of subgraphs of the resonance graph of B isomorphic to the Cl(B)-dimensional hypercube, where Cl(B) is the Clar number of B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The original version of the Clar method is qualitative and has no direct foundation in quantum theory. Eventually, much effort was devoted to providing a quantitative and theoretically founded re-formulation of the Clar model (see the recent works [18][19][20][21][22][23][24][25][26] and the references cited therein). In earlier studies, 13,14,27,28 examples of benzenoid hydrocarbons were found in which the predictions of Clar theory were violated.…”
Section: Introductionmentioning
confidence: 99%
“…The original version of the Clar method is qualitative and has no direct foundation in quantum theory. Eventually, much effort was devoted to providing a quantitative and theoretically founded re-formulation of the Clar model (see the recent works [18][19][20][21][22][23][24][25][26] and the references cited therein). In earlier studies, 13,14,27,28 examples of benzenoid hydrocarbons were found in which the predictions of Clar theory were violated.…”
Section: Introductionmentioning
confidence: 99%
“…It was proved in [15] that the resonance graphs of a special class of benzenoid graphs, fibonacenes, are precisely Fibonacci cubes. On the other hand, as proved in [21], the Clar number Cl(B) of a benzenoid system B is equal to the number of subgraphs of the resonance graph of B isomorphic to Q Cl(B) . Hence enumeration of hypercubes of all dimensions in Fibonacci cubes is essential there.…”
mentioning
confidence: 99%
“…Characterization and enumeration of Clar covers [1][2][3][4][5][6][7][8] of an arbitrary benzenoid containing up to about 500 carbon atoms became almost a routine task after introducing the concept of the Clar covering polynomial (aka Zhang-Zhang polynomial or briefly ZZ polynomial) [9][10][11][12][13] and development of ZZDecomposer, 14,15 an automatized computer program using recursive properties of ZZ polynomials to compute them in a robust manner. 4,9,[16][17][18] ZZDecomposer is freely available 19,20 and can be used for a convenient graphical definition of an arbitrary benzenoid by mouse selection of desired hexagonal faces or edges of the underlying hexagonal honeycomb lattice followed by brute-force recursive computation of the ZZ polynomial, finding recursive ZZ polynomial decomposition pathways, and producing camera-ready images of such pathways.…”
Section: Introductionmentioning
confidence: 99%